Efek Pengaruh Interpersonal pada Konsumsi Ekstravaganza di Mediasi Konsumsi Status: Penelitian - Farah Hayu Nur Hidayati; Waluyo Budi Atmoko; Fidela Berliani Prasaja Putri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine the interpersonal influence on extravagant consumption with status consumption as a mediating variable. The method used is a quantitative approach with regression analysis techniques with mediating variables. Sampling using a questionnaire with a Likert scale of 1-5. The sample obtained was 200 respondents who used the extravaganza brand. The results showed that, (1) Interpersonal influence has a positive and significant effect on extravagant consumption, (2) Interpersonal influence has a positive and significant effect on status consumption, (3) Status consumption has a positive and significant effect on extravagant consumption, (4) Status consumption partially mediates the relationship between interpersonal influence on status consumption..